The Influence of Work Environment and Work Discipline on Employee Performance at PT Satu Pilar Indonesia - Melinda Puspitasari; Eka Dyah Setyaningsih; Vina Islami (Jurnal Multidisiplin Sahombu, 2025)
There are problems with a work environment that is not conducive, such as a lack of facilities to support facilities and infrastructure, and a lack of team member discipline, which is indicated by high rates of team member absenteeism. This research aims to determine whether the work environment and Discipline influence employees' performance at PT Satu Pilar Indonesia, either partially or simultaneously. PT Satu Pilar Indonesia is a bodywork company located in Jakarta. They provide bodywork manufacturing services for various types of vehicles, both for personal, corporate, and special project needs. Bodywork is part of the automotive industry that focuses on manufacturing and modifying vehicle bodies, especially those not produced directly by the manufacturer. The researcher's motivation for researching at PT Satu Pilar Indonesia is to analyze and identify the influence of the work environment and discipline on team member performance. The sample selected used a saturated sampling technique because the population is relatively small. The sample used in this study amounted to 35 employees of PT Satu Pilar Indonesia. The study results showed that the work environment variable partially had a positive and significant effect on the performance of PT Satu Pilar Indonesia employees. The work discipline variable partially had a positive and significant effect on the performance of PT Satu Pilar Indonesia employees. The work environment and work discipline variables simultaneously had a positive and significant effect on the performance of PT Satu Pilar Indonesia employees.